Material connexion : the global resource of new and innovative materials for architects, artists and designers - Beylerian, George M.; Sherr, Leslie H.; Material ConneXion (Firm) (London, Thames & Hudson, 2005)
A first title in the ambitious new series that identifies and examines the innovative materials that are transforming art, design, and technology practice. Materials technology is the single most important agent of change in our entire designed landscape, from the buildings in which we live and work to the clothes we wear. This volume on architecture features carefully selected buildings that showcase the innovative use of a particular material. The book focuses on specific categories of materials and features an extensive range of projects, from the Netherlands Institute for Sound and Vision to the Ordos Art and City Museum in Mongolia.--
"Material ConneXion is a consultancy agency with expertise in innovative and sustainable materials. The agency's library of innovative and sustainable materials and processes is the largest of its kind in the world"--Page 4 of cover.
Includes bibliographical references (page 218).
Keywords: Building materials; Architectural design; Materials -- Technological innovations; Architecture -- Technological innovations; Architecture -- Technological innovations; Building materials